Association of Adherent-invasive Escherichia coli with severe Gut Mucosal dysbiosis in Hong Kong Chinese population with Crohn's disease. (1st January 2021) - Zhilu, Xu; Xiangqian, Dong; Keli, Yang; Caroline, Chevarin; Jingwan, Zhang; Yu, Lin; Tao, Zuo; Cheung, Chu Lok; Yang, Sun; Fengrui, Zhang; Kl, Chan Francis; Jy, Sung Joseph; et al.
ABSTRACT: Adherent invasive Escherichia Coli (AIEC) has been implicated in the pathogenesis of Crohn's disease (CD) in Western populations. Whether the presence of AIEC is also seen in CD populations of different genetic susceptibility and has negative impact on host microbiota ecology and therapeutics are unclear. AIEC presence was assessed in ileal tissues of 60 Hong Kong Chinese patients with CD and 56 healthy subjects. Mucosa microbiota was analyzed by 16s rRNA sequencing. Impact of AIEC on the gut microbiota was determined in a mouse model. AIEC was significantly more prevalent in ileal tissues of patients with CD than controls (30% vs 7.1%). Presence of AIEC in ileal tissues was associated with more severe mucosa microbiota dysbiosis in CD with decreased diversity and lower abundance of Firmicutes including butyrate producing Roseburia and probiotic Bacillus . A random forest model predicted the presence of AIEC with area under the curve of 0.89. AIEC exacerbated dysbiosis in dextran sodium sulfate (DSS)-induced colitis mice and led to resistance to restoration of normal gut microbiota by fecal microbiota transplantation (FMT). Proportion of donor-derived bacteria in AIEC-colonized mice was significantly lower than that in uninfected mice. AIEC was prevalent and associated with severe mucosa microbiota dysbiosis in CD in Hong Kong Chinese population. The presence of AIEC impeded restoration of normal gut microbiota. AIEC may serve as a keystone bacterium in CD and impact the efficacy of FMT.